SAS Operation Storm - Cole, Roger (Hodder & Stoughton, 2011)
Roger Cole, one of the SAS soldiers who took part, and writer Richard Belfield have interviewed every SAS survivor who fought in the battle from the beginning to the end-the first time every single one of them has revealed their experience. The authors have also talked to many other survivors from both sides, including the pilots who flew with the SAS, the SAS soldiers who joined the battle towards the end, and some of the insurgents who fought against them. SAS Operation Storm is a classic story of bravery against impossible odds-minute by minute, bullet by bullet.